Systematic Review of Linezolid Population Pharmacokinetics in Pediatric: Models, Covariates, and Dosing Implication - Primasari, Firdhani Satia; Hakim, Arief Rahman (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Background: The increasing prevalence of bacterial resistance has positioned linezolid as a promising antibiotic for treating infections, including in pediatric patients. Knowledge of pharmacokinetic parameters is very useful in optimizing the dose to be used in patient therapy. However, pharmacokinetic data to guide optimized dosing in children remain limited.Objectives: This review aims to summarize population pharmacokinetic (PopPK) models of linezolid in pediatric populations and identify significant covariates influencing its pharmacokinetics.Methods: A systematic search was conducted in PubMed and ScienceDirect databases for studies published between 2014 and May 2025 using the keywords